Everyday emotional intelligence - including; Daniel Goleman; Annie Mckee; Shawn Achor (Harvard Business Review Press, 2017)
With this double volume you'll get HBR's 10 Must Reads on Emotional Intelligence and the HBR Guide to Emotional Intelligence. That's 10 definitive HBR articles on emotional intelligence by Goleman and other leaders in the field, curated by our editors--paired with smart, focused advice from HBR experts about how to implement those ideas in your daily work life